UNDERPRICING DALAM PENAWARAN SAHAM PERDANA DAN PENAWARAN SAHAM SUSULAN - Gumanti, Tatang Ary; Alkaf, Nafisah (UI Scholars Hub, 2011)
Underpricing has become a subject for various examinations in initial public offerings (IPO) context. Underpricing is known as one of three anomalies surrounding IPO setting. A number of theories have been put forward to explain why such phenomenon occurs. One of them is that underpricing is used as a signal of firm quality, hoping that when the firm is going to reissue stock in the future, namely right issue or seasoned equity offerings (SEO), it will gain positive response from the market. This study aims at examining a sample of 85 IPOs and SEOs whether underpricing could signal firm quality when making right issue during 1990-2006 at the Indonesian Stock Exchange. Consistent with other capital market studies, results show that, on average, IPO firms are significantly underpriced as much as 22.35 percent, whilst for SEOs the average underpricing is 13.35 percent. The level of underpricing between IPOs and SEOs is not significantly different from zero. IPO firms experiencing higher underpricing will experience lower underpricing in SEO. Overall, the finding does not support the hypothesis that IPO underpricing is used as signal for firm quality undertaking SEO.